On the Brink of War? Decoding the Irreconcilable Differences in China-U.S. Relations - Liu, Mingyue (International Journal of Social Sciences and Public Administration, 2024)
China and the United States have one of the most important and complicated bilateral relations in the world. Two distinct, yet similarly antagonistic, stances dominate Washington and Beijing. Over the last decade, China-U.S. relations are increasingly defined by mutual mistrust and suspicion. Currently, Beijing and Washington have been trapped into enduring rivalry. Unfortunately, their rivalry is more than a set of diplomatic disputes. Commerce, as well as other differences, is also driving the two nations further apart. Their differences are now irreconcilable for neither side could grant a concession on major issues. Up to now, nothing is sufficient to resolve their disputes nonviolently.